PHASE II TRIAL OF GVHD PROPHYLAXIS WITH POST-TRANSPLANTATION CYCLOPHOSPHAMIDE FOLLOWING REDUCED-INTENSITY BUSULFAN/FLUDARABINE (BU/FLU) CONDITIONING FOR HEMATOLOGICAL MALIGNANCIES - Alousi, Amin M. (Biol Blood Marrow Transplant, 2015)
GVHD-prophylaxis with post-transplant cyclophosphamide (CY) following ablative HLA-matched bone marrow (BM) transplantation has been reported to have comparable rates of acute GVHD with an apparent reduction in chronic GVHD and infections. We conducted a phase II trial of post-CY following reduced-intensity conditioning (RIC) using intravenous busulfan (AUC of 4,000 micromolar-minutes), Fludarabine (40mg/m(2)) for 4 days and CY 50mg/kg on days +3 and +4 following BM or peripheral blood (PB) transplants from matched related (MRD) or unrelated donors (MUD). MUD- recipients received anti-thymocyte globulin (ATG); however, a later amendment removed ATG. 49 patients were treated (AML/MDS: 82%). Median age was 62 years (range, 39–72). Fifteen patients received a MRD (9 PB/6 BM); 34 had a MUD (2 PB/32 BM). The cumulative incidence of grade II–IV, III–IV acute and chronic GVHD was 58%, 22% and 18%. A matched-cohort analysis compared outcomes to tacrolimus/methotrexate GVHD prophylaxis and indicated higher rates of acute GVHD grade II–IV (46% versus 19%, HR=2.8, p=0.02) and treatment-related mortality (HR 3.3, p=0.035) and worse overall survival (HR=1.9, p=0.04) with post-Cy. The incidence of chronic GVHD and CMV reactivation did not differ. This study suggests that post-transplant CY should not be used as sole GVHD-prophylaxis following a RIC transplant from HLA matched donors.